The European Concerted Action on Anticoagulation (ECAA) Evaluation of a Set of Lyophilized Normal Plasmas to Establish the Normal Prothrombin Time for Coagulometer Systems - Poller, L.; Barrowcliffe, T. W.; van den Besselaar, A. M. H. P.; Jespersen, J.; Tripodi, A.; Houghton, D.; ECAA by the above steering committee; Prepared on behalf of (Thrombosis and Haemostasis, 1998)
Establishing the mean normal prothrombin time (MNPT) from fresh samples for prothrombin ratios and INR often presents difficulty in selection and collection of donors. A set of seven lyophilized normal plasmas has therefore been prepared at the ECAA Central Facility and studied at 143 laboratories in sixteen European states using coagulometers in serial field exercises. All centres tested either the high ISI ECAA rabbit or low ISI ECAA human reference thromboplastin. The MNPT of fresh plasmas and means of the lyophilized samples were closely comparable with most routine rabbit thromboplastins. Using human thromboplastins means with the lyophilized normals were marginally but significantly longer and with the bovine Thrombotest significantly shorter than the MNPT of fresh plasmas causing alterations in INR. There was no appreciable effect on INR of 2.5 and 3.5 when lyophilized normals were substituted for fresh normals with the rabbit reagents.